1992
DOI: 10.1152/jappl.1992.73.4.1402
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bilateral vagotomy on oxygenation, arousal, and breathing movements in fetal sheep

Abstract: To investigate the effects of bilateral cervical vagotomy on arousal and breathing responses, we studied eight sham-operated and eight chronically instrumented unanesthetized vagotomized sheep fetuses between 136 and 144 days of gestation (term approximately 147 days). Each fetus was instrumented to record sleep states, diaphragmatic electromyogram, blood pressure, pH, and blood gas tensions. In a randomized order, fetal lungs were distended with four different O2 concentrations: 0 (100% N2), 21, 50, and 100% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…(1974) showed that vagal denervation or blockade of nerve conduction had no significant effect on the size, frequency or incidence of fetal breathing movements (FMBs). Similarly, in our previous study, no significant effect on the overall incidence of FBMs was observed in the vagally denervated fetal sheep although individual episodes and inspiratory times (T,) were shorter as compared with the sham-operated group (Hasan & Rigaux, 1992).…”
Section: Vagal Feedback and Fetal Breathing Movements (Fbms)supporting
confidence: 65%
See 1 more Smart Citation
“…(1974) showed that vagal denervation or blockade of nerve conduction had no significant effect on the size, frequency or incidence of fetal breathing movements (FMBs). Similarly, in our previous study, no significant effect on the overall incidence of FBMs was observed in the vagally denervated fetal sheep although individual episodes and inspiratory times (T,) were shorter as compared with the sham-operated group (Hasan & Rigaux, 1992).…”
Section: Vagal Feedback and Fetal Breathing Movements (Fbms)supporting
confidence: 65%
“…198 1;Hasan & Rigaux, 1992) examined only the short term effects of vagal innervation on breathing patterns. It is not clear whether the removal of vagal afferent feedback over a relatively long period would have an impact on the central respiratory pattern generator since the nucleus tractus solitarius (NTS), one of the four vagal nuclei, receives critical rhythm modulatory and regulatory afferents from upper and lower respiratory tracts.…”
Section: Vagal Feedback and Fetal Breathing Movements (Fbms)mentioning
confidence: 99%
“…Second, premature birth did not significantly alter the vagal Hering-Breuer reflex in lambs 2, and the PCF-mediated respiratory responses already existed in newborn lambs (2) and rabbits (15). Third, breathing movements are episodic in fetal life and abruptly change to be continuous after delivery, but continuous breathing is critically dependent on fetal maturity and intact vagal nerve function (21,54). For example, the consequences of bivagotomy were more dramatic in the newborn anesthetized and decerebrated cats, dogs, and kittens compared with the older ones, including a greater prolongation of TE, possibly leading to death within a few hours (12,50).…”
Section: Discussionmentioning
confidence: 93%
“…The treatment of these disorders has been largely symptomatic due to incomplete understanding of the basic mechanism involved in the control of neonatal breathing. Breathing movements are episodic in fetal life and abruptly change to be continuous after delivery, but continuous breathing is critically dependent upon fetal maturity and intact vagal nerve function (Hasan and Rigaux, 1992).…”
mentioning
confidence: 99%